The rise of demonstrative-based first/second-person markers in the history of Japanese: A speaker subjectivity account - Yamaguchi, T. (John Benjamins Publishing, 2015)
This paper explores the rise of demonstrative-based person markers in the history of Japanese and takes Ishiyama's spatial semantic approach as its point of departure. Despite the claim that demonstrative-based person markers remained functionally demonstrative, I argue that they began to manifest the category of person from an early stage of their development; that is to say, thanks to speaker innovation, demonstratives underwent semantic re-analysis to become markers representing the speaker's ego in the reality of discourse. This paper also pinpoints that two notions, distancing and dissimilarity, are not spelled out in Ishiyama's framework. In conclusion, the substitution of the first-person marker for the second-person marker is analysed tentatively using Keller's theory of linguistic signs.